Professor John Prebble’s Guiding Hand in New Zealand’s Advance (Binding) Rulings Regime - Sawyer, Adrian (Victoria University of Wellington Law Review, 2022)
At first glance, one could be excused for concluding that New Zealand’s advance (binding) rulings regime can be traced to a Government budget announcement in 1992. In reality, the early efforts of Professor John Prebble in the mid-1980s laid the groundwork that eventually resulted in a binding rulings regime commencing in 1995. John’s contributions not only provided input from reviewing comparative jurisdictions, but also a draft code. Furthermore, post-regime, John was instrumental in endorsing the regime through his membership of the Committee of Experts on Tax Compliance (the Committee). Beyond this, further refinements to the regime (including more cost-efficient and accessible short process rulings) to a large degree reflect John’s early observations. That is, businesses need certainty when making decisions that affect their tax obligations imposed by complex legislation and they should have access to a facility that can enhance that certainty.